(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The amount of dedication and interest displayed by workers in their organisation and the idealsit promotes is referred to as employee engagement and the word comes from the phrase engagedemployees. In addition to investigating the link between employee engagement and performance, theoutcomes of this research will analyse the variables that influence employee engagement.In addition tocompensation and benefits, evaluations look at health and safety conditions as well as the company’soverall performance, as well as internal communication, leadership development, and other aspects ofthe job. As part of this study’s design, it included both the causal and descriptive parts of research.Inorder to obtain the data, a standardised questionnaire was used, and the number of workers thatcomprised the sample was predetermined to be 100. When doing an analysis of the data, descriptivestatistics are an important tool to have at your disposal.